Indonesia Cybersecurity Policy Toward Data and Privacy Protection, Literature Review Study - Meliala, Brandon Nathanael (International Journal of Research and Applied Technology (INJURATECH), 2024)
This study reviews the development of Indonesia cybersecurity policy in relation to data and privacy protection through a structured literature review of academic articles, government regulations, and policy reports. The analysis focuses on regulatory evolution, institutional roles, and implementation challenges following the enactment of the Personal Data Protection Law and the strengthening of national cyber agencies. Findings indicate that Indonesia has shifted from fragmented rules toward a more unified governance framework emphasizing management, critical infrastructure protection, and individual data rights. However, persistent gaps remain in enforcement capacity, inter-agency coordination, and public awareness, which limit policy effectiveness. The literature also highlights tensions between digital economic growth and liberties, particularly in data flows and surveillance practices. This review contributes by synthesizing evidence on how cybersecurity policy supports privacy objectives in Indonesia and by identifying future research directions on compliance mechanisms and the balance between security and personal data protection in digital ecosystem